2011
DOI: 10.1080/10253866.2011.574824
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acculturation theory: (crossing) conceptual boundaries

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Consumer acculturation theorists have developed an insightful body of literature about the ways in which migrants adapt to foreign cultures via consumption. The present paper revisits fourteen key studies from this field to highlight its most important contributions, critique its conceptual boundaries, and present cases of conceptual border crossings that indicate an emerging need for a broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
164
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 61 publications
1
164
1
3
Order By: Relevance
“…These consumption experiences do not necessarily relate to distant geographical micro-places where other kinds of autobiographical consumption can occur. Such decontextualized consumption engagements are documented extensively in the literature on consumer acculturation, describing how the migrant is able to recreate, by means of consumption, a self that can seem disconnected and "outdated" (Luedicke, 2011). By taking the less visited path of contextualized consumption experiences during travel, the paper illustrates how consumption experiences support family members in the process of negotiating their history as a family.…”
Section: Introductionmentioning
confidence: 94%
“…These consumption experiences do not necessarily relate to distant geographical micro-places where other kinds of autobiographical consumption can occur. Such decontextualized consumption engagements are documented extensively in the literature on consumer acculturation, describing how the migrant is able to recreate, by means of consumption, a self that can seem disconnected and "outdated" (Luedicke, 2011). By taking the less visited path of contextualized consumption experiences during travel, the paper illustrates how consumption experiences support family members in the process of negotiating their history as a family.…”
Section: Introductionmentioning
confidence: 94%
“…Such transitions are dependent on contextual factors from the migrants' origin and host cultures and are systemically influenced by these cultures and their institutions, including the government, school and religious structures, ethnic communities, mass media, and the market in general (Luedicke 2011). The post-assimilationist view in consumer research has contributed to our understanding of migration-related identity transitions by illustrating the plasticity involved in the experience of migration and how consumption supports acculturation.…”
Section: Acculturation Agents In Consumer Researchmentioning
confidence: 99%
“…While most research on acculturation emphasizes consumer agency, Luedicke (2011) suggests that under certain circumstances, migrants may not easily be able to bridge the logics of the home and host cultures due to the lack of economic, cultural, and social resources. Migration research has shown, for instance, how women with scarce capital (particularly economic and cultural) struggle to acculturate to new contexts.…”
Section: Acculturation Agents In Consumer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Peñaloza (1989, p. 116) conceptualised consumer acculturation agents as "those individuals or institutions who serve as sources of consumer information and/or models of consumption behavior". The possible outcomes of consumer acculturation are either that an acculturating individual accepts or rejects the host culture, or that the individual retains or rejects the original culture (Luedicke 2011;Peñaloza 1994).…”
Section: The Chinese Consumer Socialisation Processmentioning
confidence: 99%